ANALISIS PERENCANAAN DAN PENGENDALIAN BIAYA PEMELIHARAAN AKTIVA TETAP (MESIN) UNTUK MENJAGA KELANCARAN PRODUKSI PADA PT. TROPICA COCOPRIMA - Walukow, Anggreanny Pratiwi; Poputra, Agus; Sabijono, Harijanto (Universitas Sam Ratulangi, 2013)
This researchwas case studyon PT. Tropica Cocoprima, the title is â€œAnalysis ofÂ Planning and Contolling Maintenance Cost of Fixed Assets (Mechanical) To Maintain Smooth Productionâ€. PT. Tropica Cocoprima is a company that produces flour as the end product of the production process. In the production process, production machinery plays an important rolein providing products there for eurgently needed care in order to avoid frequent damage. This purpose of research is to analysis routin cost of eengine maintenance cost for planning and control at PT. Tropica Cocoprima. To plan and controlling cost , need to the holding of separation between variable cost and fixed cost. This research used the least squares method for separate the variable cost and fixed cost. Calculations with using analysis three difference, was found that the companies getting difference inprofitable for costs maintenance of machine fixed namely on difference efficiency because the unit that produced is 1.750.000 kg greater than the planned unit is 1.166.415 kg.